Factors associated with lung cancer among firefighters: a systematic literature review - Augustine W. Kang; Natalie S. Lui (BMC Public Health)
Abstract This short review addresses the pressing issue of lung cancer among firefighters, a population facing unique occupational hazards such as smoke inhalation and asbestos exposure. With lung cancer being a leading global cause of death, the study emphasizes the disproportionate burden on firefighters. Notably, wildfire smoke, containing carcinogenic elements, poses a rising significant threat to firefighters’ respiratory health. Despite evidence linking firefighting to increased lung cancer risk, few studies have explored the underlying mechanisms. This study conducts a comprehensive review employing PRISMA guidelines to synthesize existing literature from 1972 to 2022. We discuss the association between age, race, and time spent fighting fires with lung cancer development. Our review also underscores the scarcity of studies investigating specific carcinogens and their role in firefighters’ lung cancer risk, emphasizing the need for more targeted research. The study advocates for improved methodology, suggesting the use of individual-level exposure metrics like “fire-hours” to enhance causal inference. Despite limitations in current literature, the findings stress the urgency of understanding the intricacies of lung cancer development among firefighters and call for further research to inform preventive measures and potential screening protocols.